Pretreatment with a Small Dose of Ketamine to Prevent Withdrawal Movement caused by the Rocuronium Injection during Induction (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Rocuronium causes pain on injection during the induction of anesthesia. This study was carried out to evaluate the efficacy of a small dose of ketamine in managing injection pain and withdrawal movement during induction.Materials and Methods: This observational study was carried out from August 2022 to November 2022 at Nepal Medical College and Teaching Hospital. The inclusion criteria for the study were ASA I and II. 67 patients (aged 16-65 years) scheduled for elective surgery were included in the study after following the inclusion and exclusion criteria. Then the intravenous ketamine was given without venous occlusion, 30 seconds after followed by rocuronium 0.6 mg/kg intravenous. Then the patient's response to rocuronium injection was recorded on a five-point scale, as well as a change in the vital parameters was collected. Results: The incidence of pain was significantly less in 49 patients (73.13%), and remaining 18 (26.86%) patients out of 67 patients still had pain after intravenous Ketamine 0.5mg/kg, the incidence was more in the younger patients’ groups than older patients’ groups. The cause of this incidence was still to find out. The pain score was significantly less in patients receiving ketamine.Conclusion: We concluded that pretreatment with ketamine 0.5 mg/kg without venous occlusions is effective in decreasing the incidence of pain caused by rocuronium injection